COMPREHENSIVE REVIEW OF ARTIFICIAL INTELLIGENCE IN RADIATION PLANNING - Mohammed Jaber Ahmed Muyini, HAMED THEB ALMUTIRI, Abdulrahman Ibrahim Abbas, MOSA SALEM ALQARNI, HAMZA ALI AL OMAR, Mubarak Ayed Assiri (Chelonian Research Foundation, 2023)
Radiation therapy is the backbone of cancer treatment, pointing to murder-threatening cells while saving sound tissue. The complexity of the radation establishment must be carefully calculated and decided. Artificial intelligence (AI) has long played a key part in progressing the effectiveness and adequacy of radio programming. This comprehensive assessment incorporates different coordination strategies, computational machine learning and profound learning models, and these are combined with radation relapse procedures. This survey looks at the benefits, challenges, and advances of AI-driven vitality administration, highlighting progress in bolster frameworks. In expansion, it gives proposals for future investigative bearings and viable bits of knowledge, clearing the way for an advance towards successful and restorative treatmen